Unveiling Firm Value Drivers: The Interplay of Capital Structure, Dividend Policy, and Firm Size Moderated by Economic Profitability in Indonesia’s Consumer Goods Sector - Dini, Siti; Anwar, Jenny; Chen, Jesslyn; Ginting, Wenny Anggeresia (Yayasan Riset dan Pengembangan Intelektual, 2025)
The purpose of this study is capital structure, dividend policy and firm size on firm value with profitability as a moderating variable in manufacturing companies in the Consumer Goods Industry Sector. This research approach is based on a quantitative approach. The population is the Manufacturing Consumer Goods Industry Sector listed on the Indonesia Stock Exchange in 2019-2022 as many as 94 companies. The research sample obtained was 28 companies with 112 observations. The data collection technique is a documentation study. The data analysis technique uses multiple linear regression analysis. The results obtained Capital Structure, Dividend Policy has no effect on Firm value, Firm size has a positive effect on Firm value, Profitability cannot moderate the effect of Capital Structure and Dividend Policy on Firm value and Firm size can moderate the effect of Capital Structure on Firm value.